Kazakhstan Labor Market Outcomes : Achievements and Remaining Challenges - Strokova, Victoria; Elzir, Angela; Margolis, David (World Bank, Washington, DC, 2017)
This note presents a detailed analysis of jobs in Kazakhstan at the macro and individual levels, including regional and socio-economic disparities. At the macro level, it includes a diagnostic of the links between economic growth, jobs, and productivity across different economic sectors. At the individual level, the analysis focuses on labor market outcomes of women and men, young and adult workers, residents of urban and rural areas, and people in the bottom 40 percent of the consumption distribution. It also presents a detailed analysis of determinants of employment and wages. The rest of the note is organized as follows: section two discusses the relationship between economic growth, jobs, and productivity across different economic sectors. Section three discusses demographic trends and overall labor market outcomes. Section four focuses on assessing spatial and sectoral differences in access to jobs, including for those in the bottom 40 percent. Section five concludes with a discussion of challenges and broad policy implications.